Smart Computing and Informatics Proceedings of the First International Conference on SCI 2016, Volume 1 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Das, Swagatam (Smart Innovation, Systems and Technologies, 2018)
This volume contains 74 papers presented at SCI 2016: First International Conference on Smart Computing and Informatics. The conference was held during 3-4 March 2017, Visakhapatnam, India and organized communally by ANITS, Visakhapatnam and supported technically by CSI Division V - Education and Research and PRF, Vizag. This volume contains papers mainly focused on applications of advanced intelligent techniques to video processing, medical imaging, machine learning, sensor technologies, and network security.